Trajectory modification method based on frequency domain analysis for precision contouring motion control systems. (September 2021) - Wang, Ze; Hu, Chuxiong; Zhu, Yu
Highlights: Trajectory modification method based on time-frequency analysis is first applied to multi-axis contour motion control. Different from the traditional time domain analysis method, the contouring control performance is analyzed in frequency domain. The design of traditional contouring error estimator and controller are avoided to facilitate the application on real time control. Abstract: For multi-axis motion system widely used in CNC machine tools, contouring following control is an important research topic. For most existing contouring motion control methods, it is usually necessary to estimate the contouring error of multi-axis system and then design contouring controller to suppress it. However, additional contouring error estimator and controller requiring complicated hardware adjustment is not suitable for existing commercial CNC systems with built-in control systems. In this paper, a frequency domain analysis based trajectory modification method is proposed to improve contouring control performance through a way that is easier to implement. In the proposed method, the modified trajectory can be calculated off-line just according to the instantaneous frequencies of the reference trajectories and the closed loop frequency characteristics of each axis. After the modification, the amplitude attenuation of the actual position output can be effectively suppressed, and the output of each axis has the same phase lag, thus improving the contouring control performance. Compared with other existing contouring control methods, the main contribution of this paper is to analyze and control contouring error from the angle of frequency. Various of simulations and comparative experiments are conducted to verify the effectiveness of the proposed contouring control method. The experimental results demonstrate the advantages of the proposed scheme over other methods, i.e. excellent contouring control performance can be achieved without additional contouring error estimation and control.